1965
DOI: 10.1002/app.1965.070091117
|View full text |Cite
|
Sign up to set email alerts
|

Environmental surface effects on ABS resins

Abstract: SynopsisSpectroscopic analyses of weathered samples and thermal oxidation of the various phases found in ABS resins indicate that these plastics deteriorate most readily through their polybutadiene component. The change in physical properties and color of these resins with age can be correlated with the decomposition of the polybutadiene-containing phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…While the loss of mechanical properties in ABS is often attributed to thermo‐oxidative degradation in the PB phase, thermo‐oxidative degradation and physical aging can also occur in the SAN phase 15–17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the loss of mechanical properties in ABS is often attributed to thermo‐oxidative degradation in the PB phase, thermo‐oxidative degradation and physical aging can also occur in the SAN phase 15–17…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been directed toward understanding how chemical aging occurs in ABS and how its effects can be minimized. Gesner,15 Alekseev et al,16 and Tiganis et al17 have shown that the thermo‐oxidation of ABS occurs in the polybutadiene (PB) phase of the resin. The results of another study regarding degradation of ABS during processing showed that PB was the least stable component toward thermal oxidation 18…”
Section: Introductionmentioning
confidence: 99%
“…Based on an evaluaUon of stabilized commercial ABS samples having various compositions. Gesner ( 1) proposed that differences in percent graWng account for the stability differences (induction times) observed. Htrai (8) reanalyzed the data and proposed that the rates of thermal oxidation of stabilized ABS samples are proportional to the rubber content consisting of additives dispersed in two-phase elastomer-thermoplastic blends.…”
Section: Introductionmentioning
confidence: 99%
“…They reported an activation energy of 41.84 KJ/mol or less for the initiation process from which hydroperoxide was formed. Gesner has reported the effect of aging on ABS plastics properties (5). Casale and coworkers have studied ABS degradation during processing and during natural and artificial light aging (6).…”
Section: Introductionmentioning
confidence: 99%